A geometrical inverse kinematics method for hyper-redundant manipulators - Yahya, S.; Mohamed, H.A.F.; Moghavvemi, M.; Yang, S.S. (2008)
Hyper-redundant manipulators have large number of kinematic degrees of freedom, thus processing some unconventional features such as the ability to enter a narrow space while avoiding obstacles. To solve the problem of multi-solution caused by redundancy, a geometrical method is presented in this paper. This proposed method finds one optimal solution to the inverse kinematics of redundant or hyper redundant manipulators from these infinite solutions with fewer computations. This method can be used for any planar n-serial manipulators. Experiments are conducted 3-links redundant manipulator and 10-links hyper-redundant manipulator to demonstrate the effectiveness of this proposed method.